Pathogenicity of the SARS-CoV-2 Virus Variants of Concern for the Syrian Golden Hamster - A. V. Shipovalov; G. A. Kudrov; A. A. Tomilov; S. A. Bodnev; N. D. Boldyrev; A. S. Ovchinnikova; A. V. Zaikovskaya; O. S. Taranov; E. K. Ivleva; O. V. P’yankov; R. A. Maksyutov (Проблемы особо опасных инфекций, 2022)
The aim of the work was to study the pathogenicity of newly emerging variants of SARS-CoV-2 on the model of the Syrian golden hamster.Materials and methods. We used the strains of SARS-CoV-2 virus related to the VOC circulating in the territory of the Russian Federation. The experiments were carried out on outbreed Syrian hamsters obtained from the nursery of the SSC VB “Vector”. The infectious titer of coronavirus in tissue samples collected from infected laboratory animals was determined on a Vero E6 cell culture. The Ct in RT-PCR was considered an additional parameter for monitoring the viral load in the samples. The severity of lung tissue damage in Syrian hamsters with COVID-19 was assessed by histological preparations.Results and discussion. 50 % infecting doses in case of the intranasal infection have been determined, histological analysis of lung tissues performed. The pathogenicity of various variants of the SARS-CoV-2 virus for the Syrian hamster has been evaluated, differences in infecting doses and pathological changes in the lungs have been revealed. SARS-CoV-2 viruses belonging to Beta genetic variant have the highest virulence, while Alpha variant has the lowest one when comparing the studied strains by the ID50 value. The Delta and Omicron variants have a matched ability to cause specific damage to the tissues of the respiratory tract, while being inferior only to the Beta variant. It has been demonstrated that Syrian hamsters are an adequate model for assessing the pathogenicity of the SARS-CoV-2 virus variants of concern. Variants of SARS-CoV-2 virus during intranasal infection has shown different degree of pathogenicity in the Syrian hamster model.